2005
DOI: 10.1111/j.0269-283x.2005.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria transmission dynamics in central Côte d'Ivoire: the influence of changing patterns of irrigated rice agriculture

Abstract: The dynamics of malaria transmission was studied comparatively in the villages of Zatta and Tiemelekro, central Cote d'Ivoire, from February 2002 to August 2003. Prominent agroecosystems in these villages are irrigated rice growing and vegetable farming, respectively. Mosquitoes (Diptera: Culicidae) were collected on human bait at night and by pyrethrum knock-down spray sheet collections at four randomly selected sentinel sites in each village. In 2002, for a total of 96 man-nights per village, 7716 mosquitoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
3
38
0
3
Order By: Relevance
“…Since the bulk of the current global burden of malaria is borne by countries in Africa and since flooded rice paddies serve as larval habitats and are a known risk factor for malaria transmission (Koudou et al, 2005), we selected a rice-growing region in central Kenya (Mwea) as our study site. Rice paddy water and An.…”
Section: Resultsmentioning
confidence: 99%
“…Since the bulk of the current global burden of malaria is borne by countries in Africa and since flooded rice paddies serve as larval habitats and are a known risk factor for malaria transmission (Koudou et al, 2005), we selected a rice-growing region in central Kenya (Mwea) as our study site. Rice paddy water and An.…”
Section: Resultsmentioning
confidence: 99%
“…These are also the most common species in western African rice cultivation areas. 19,20 Among these two species, An. gambiae s.l was predominant, accounting on average for 90% (n ‫ס‬ 366,657) and was particularly abundant during the rainy season of 1999 and 2000 and the dry hot season of 1999 (second agricultural cycle).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas a negative association between adult density and HBI has been observed in the Office du Niger, Mali 6,19 and Burkina Faso, 23 a recent study conducted in Côte d'Ivoire suggested a positive association reporting HBI up to 95% during high-density periods. 20 The vectorial capacity was relatively low with a seasonal and village-to-village variation. The median vectorial capacity was higher in the non-renovated zone of Molodo than in the renovated zones of Niono and Ndebougou, but the statistical significance was borderline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cependant, même s'ils permettent une augmentation importante de l'énergie, de la production de céréales et de produits maraîchers, les barrages hydroagricoles ont parfois des répercussions profondes sur l'endémie palustre, du fait de la création des gîtes larvaires favorables aux vecteurs du paludisme [20,21,28]. Au Cameroun, l'État a réalisé la construction d'une dizaine de barrages hydrauliques dans les années 1980.…”
Section: Introductionunclassified